2015
DOI: 10.18632/oncotarget.6752
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-199a-5p decreases esophageal cancer cell proliferation through repression of mitogen-activated protein kinase kinase kinase-11 (MAP3K11)

Abstract: Studies examining the oncogenic or tumor suppressive functions of dysregulated microRNAs (miRs) in cancer cells may also identify novel miR targets, which can themselves serve as therapeutic targets. Using array analysis, we have previously determined that miR-199a-5p was the most downregulated miR in two esophageal cancer cell lines compared to esophageal epithelial cells. MiR-199a-5p is predicted to bind mitogen-activated protein kinase kinase kinase 11 (MAP3K11) mRNA with high affinity. In this study, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…On the other end, in hepatocellular carcinoma [35] and colorectal cancer [36] mir155-5p has demonstrated its ability to resist apoptosis and promotes cellular proliferation, respectively. Intriguingly, although mir199a-5p was found to suppress tumor growth from colorectal cancer cells [37] , papillary thyroid carcinoma [38] , triple-negative breast cancer [39] and proliferation of esophageal cancer cells [40] , its down-regulation was shown to promote prostate adenocarcinoma progression [41] . Furthermore, mir29b-3p has been shown to act as a tumor suppressor in glioblastoma where it can inhibit cell growth and induce apoptosis in vitro [42] .…”
Section: Resultsmentioning
confidence: 99%
“…On the other end, in hepatocellular carcinoma [35] and colorectal cancer [36] mir155-5p has demonstrated its ability to resist apoptosis and promotes cellular proliferation, respectively. Intriguingly, although mir199a-5p was found to suppress tumor growth from colorectal cancer cells [37] , papillary thyroid carcinoma [38] , triple-negative breast cancer [39] and proliferation of esophageal cancer cells [40] , its down-regulation was shown to promote prostate adenocarcinoma progression [41] . Furthermore, mir29b-3p has been shown to act as a tumor suppressor in glioblastoma where it can inhibit cell growth and induce apoptosis in vitro [42] .…”
Section: Resultsmentioning
confidence: 99%
“…From the miRNA-mRNA regulatory network constructed in the present study, the regulation of hsa-miR-199a-5p-MAP3K11 was observed. Byrnes et al ( 21 ) demonstrated that miR-199a-5p acts as a tumor suppressor in carcinogenesis, and that its downregulation contributes to enhanced cellular proliferation by targeting MAP3K11. Further details of the results of the present study are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our functional assays showed that ectopic expression of all members of the miR‐199 family inhibited cancer cell aggressiveness, indicating that the family acted as anti‐tumor miRNA in HNSCC cells. The anti‐tumor function of miR‐199a‐5p was reported in several types of cancers . With regard to miR‐199a‐5p , recent data showed that miR‐199a‐3p was downregulated in osteosarcoma and that restoration of miR‐199a‐3p significantly inhibited CD44 expression .…”
Section: Discussionmentioning
confidence: 99%